Efficient synthetic procedure to new 2-imino-1, 3-thiazolines and thiazolidin-4-ones promoted by acetonitrile electrogenerated base12. (20th June 2018) - Haouas, Beya; Sbei, Najwa; Ayari, Hana; Benkhoud, M. Lamine; Batanero, Belen
Abstract : Regioselective sulfur–carbon bond formation from disubstituted thioureas and 1, 2-dielectrophiles. Abstract : A novel and convenient strategy is described for the regioselective conversion of N, N ′-disubstituted thioureas and 1, 2-dielectrophiles into the highly biologically valuable 2-imino-thiazoline and 2-imino thiazolidine-4-one derivatives. The synthesis proceeds through a process with good yield promoted by an electrogenerated base (EGB) obtained with high current efficiency.